2016
DOI: 10.1080/13561820.2016.1203766
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Norwegian version of the Care Process Self-Evaluation Tool

Abstract: The Care Process Self-Evaluation Tool (CPSET) assesses key characteristics of well-organised care processes in hospitals from an interprofessional team perspective. The present study investigated the psychometric properties of the CPSET in terms of factor structure, convergent and discriminant validity, and reliability in Norwegian language and context. After a pilot test, the Norwegian version of the questionnaire was administered as a web form to 501 health professionals in public general hospitals and menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, the team members reported this information inconsistently. This discrepancy may be explained by respondents’ interpretation of the term “clinical procedure”: it may be understood differently from one respondent to another [30]; it may also reflect individual respondents being unaware of the existence of a particular procedure. Further, respondents who were aware of the existence of the clinical procedure may not actually have used it in the care process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the team members reported this information inconsistently. This discrepancy may be explained by respondents’ interpretation of the term “clinical procedure”: it may be understood differently from one respondent to another [30]; it may also reflect individual respondents being unaware of the existence of a particular procedure. Further, respondents who were aware of the existence of the clinical procedure may not actually have used it in the care process.…”
Section: Discussionmentioning
confidence: 99%
“…For use in the present study, the Relational Coordination Survey was translated to Norwegian and piloted on 10 health-care professionals within a hospital by Størkson et al [30]. An authorized translation agency translated the US-English version of the Relational Coordination Survey into Norwegian language.…”
Section: Theory and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that the Norwegian version of the CPSET has acceptable psychometric attributes (convergent validity, reliability) (32). Other translated instruments that measure coordination and communication are the Relational Coordination Survey (RCS) (36,37) and the Nijmegen Continuity Questionnaire (38).…”
Section: Not All Disciplines Were Includedmentioning
confidence: 99%
“…As a pilot, we first tested the translated version using ten professionals in the specialist health service (32). These came from various disciplines at a medium-size hospital in Western Norway Regional Health Authority.…”
Section: The Cpset Questionnairementioning
confidence: 99%